ANALISIS PELANGGARAN KODE ETIK PUBLIK RELATION PADA FILM MY STUPID BOSS SEASON 1 - Amelia Hidayatus Sabila; Ainur Rochmaniah (Journal Publicuho, 2025)
The practice of PR requires integrity, professionalism, and compliance with applicable ethical standards, one of which is the code of ethics from the International Public Relations Association (IPRA). The researcher's interest in the IPRA code of ethics arises because this ethical guide is international and has become an important benchmark in assessing the quality of PR practices in various parts of the world, including in its representation in the media. This research aims to analyse the representation of violations of the PR code of ethics in the film My Stupid Boss Season 1 using Charles Sanders Peirce's semiotic approach. The results showed violations of the IPRA code of ethics in the film MyStupid Boss Season 1 include the principles of obedience, integrity, dialogue, openness, poaching and work, thus creating an authoritarian workplace, including company leaders and owners often harassing employees, arriving late and ignoring employees. The movie depicts a business reality that ignores public relations ethics, which can adversely affect internal relations and company reputation. The importance of IPRA's code of ethics in fostering moral and competent organisational communication is supported by this research.